Hak Pendidikan sebagai Hak Asasi: Studi tentang Pemenuhan Hak Mahasiswa Disabilitas di Pekalongan - Nurlailiya, Iis; Khasna, Syarifa (Sharia Faculty, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study aims to analyze the fulfillment of the right to education for students with disabilities in higher education institutions in Pekalongan. The primary issue addressed is the low accessibility of higher education for students with disabilities, which contradicts the principles of human rights: universality, interdependence, non-discrimination, and state responsibility. This research employs an empirical juridical method with a qualitative approach, combining primary data from interviews with policymakers and students and secondary data from legal documents and related literature. The findings indicate that most higher education institutions in Pekalongan have not fully ensured the right to education for students with disabilities. Existing services and facilities remain ad hoc, lacking structured regulations or inclusive standards. Three key findings include the absence of specific inclusive policies, the lack of integrated data on students with disabilities, and the unavailability of Disability Service Units. The legal implications of this inadequacy involve violations of human rights and state obligations, as mandated by Law No. 8 of 2016 concerning Persons with Disabilities. This study recommends the development of inclusive regulations and strategic measures to establish a more inclusive and sustainable educational environment, ensuring the fulfillment of the right to education for all, including persons with disabilities.